Advances in Manufacturing II Volume 5 - Metrology and Measurement Systems - Diering, Magdalena; Wieczorowski, Michał; Brown, Christopher A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers timely contributions on metrology and measurement systems, across different disciplines and field of applications. The chapters, which were presented at the 6th International Scientific-Technical Conference, MANUFACTURING 2019, held on May 19-21, 2019, in Poznan, Poland, cover cutting-edge topics in surface metrology, biology, chemistry, civil engineering, food science, material science, mechanical engineering, manufacturing, metrology, nanotechnology, physics, tribology, quality engineering, computer science, among others. By bringing together engineering and economic topics, the book is intended as an extensive, timely and practice-oriented reference guide for both researchers and practitioners. It is also expected to foster better communication and closer cooperation between universities and their business and industry partners. .
Statistical comparison of original and replicated surfaces -- Application of acoustic emission signals pattern recognition for a firearm identification -- Automated system for workpiece leveling on a machine tool -- Technological assurance of machining accuracy of crankshaft -- Nonparametric assessment of surface shaping by hybrid manufacturing technology -- Analysis of the geometry and surface of the knife blade after milling with a various strategies -- Uncertainty of sine input calibration apparatus for the air gauges -- Testing geometric precision and surface roughness of Titanium alloy thin-walled elements processed with milling.
Keywords: Engineering design; Measurement; Measuring instruments; Coatings; Tribology; Corrosion and anti-corrosives.; Engineering Design; Measurement Science and Instrumentation; Coatings; Tribology; Corrosion